Comparison of the Radiologic, Arthroscopic, and Clinical Outcomes between Repaired versus Unrepaired Medial Meniscus Posterior Horn Root Tear During Open Wedge High Tibial Osteotomy - Lee, O-Sung; Lee, Seung Hoon; Lee, Yong Seuk (The Journal of Knee Surgery, 2019)
The efficacy and outcomes for the concurrent repair of medial meniscus posterior horn root tear (MMPHRT) during open wedge high tibial osteotomy (OWHTO) are unclear. This study compared the radiologic, arthroscopic, and clinical outcomes between repaired and unrepaired MMPHRT during OWHTO. Fifty-seven patients were prospectively enrolled from 2014 to 2016. The radiologic, arthroscopic, and clinical outcomes were compared between 25 patients who underwent OWHTO with all-inside repair of MMPRT using FasT-Fix (repaired group) and 32 patients who underwent OWHTO without repair of MMPRT (unrepaired group) with a mean 2-year follow up in both groups. The meniscal healing status was classified as complete, partial, or no healing, according to second-look arthroscopic findings. The medial meniscal extrusion (MME) was evaluated using magnetic resonance imaging. The width of medial joint space, joint line convergence angle (JLCA), posterior tibial slope (PTS), Kellgren–Lawrence (KL) grade, hip-knee-ankle angle, and weight-bearing line ratio was evaluated on simple standing. The clinical outcomes were evaluated using the Knee Society score and the Western Ontario and McMaster University score. Healing rates (partial and complete) of the MMPHRT showed a statistical difference between the two groups (repaired group vs. unrepaired group, 19/25 (76%) vs. 13/32 (40.6%), p = 0.008). The postoperative MME showed no statistical differences between groups (repaired versus unrepaired group: 4.5 ± 1.3 mm vs. 4.5 ± 2.1 mm, p = 0.909). The postoperative width of medial joint space, JLCA, PTS, and KL grade all showed no statistical differences between groups after 2 years of OWHTO. Other radiologic parameters and clinical outcomes showed no statistical differences between groups. Repair of the MMPHRT during OWHTO showed a superior healing rate to the unrepaired MMPHRT. However, repair of the MMPHRT was not related to the radiologic and clinical outcomes. Therefore, there is no clear evidence of the need for the MMPHRT repair during OWHTO.
Keywords: knee; open wedge high tibial osteotomy; meniscus posterior horn root tear; repair; healing; outcome